An assessment of knowledge, attitude and practices (KAP) towards warfarin medication among patients with prosthetic valve in a tertiary care hospital of south India - M. G., Gopisankar; A., Surendiran; M., Hemachandren (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Warfarin is a drug with narrow therapeutic index. It requires varied adequate doses for achieving target INR so as to prevent episodes of thromboembolism. It is important to properly educate the patient while prescribing this drug to reduce the side effects and maintain perfect anticoagulation status. This study was done to assess the baseline Knowledge, Attitude and Practices (KAP) towards warfarin medication among patients with cardiac valve replacement in a tertiary care hospital of south India to get a baseline data which can recommend implementation of health education programs targeting these patients. Methods: An observational cross-sectional study was approved by Institute Ethics Committee JIPMER, Puducherry. It included patients on treatment with warfarin maintenance therapy for a period of not less than three months following cardiac valve replacement in the months of October 2016 to October 2017. The questionnaire included 39 questions of qualitative and quantitative basis, which was scored for a total of 50 and analysed using SPSS software. Results: About 240 patients were interviewed who attended cardiothoracic vascular surgery outpatient department and taking warfarin for at least 3 months following surgery of valve replacement. Patients were divided into two groups. Group A included patients who achieved target INR and group B are those out of target INR. 15.7 percent (35) had low score, 76.2 (160) had medium score and 15 (7.1) percent had high scores in group A. In group B 22(81.5%) had medium score and 5 (18.5%) had high score. The median score was more among patients with higher education (p=0.01). There was no significant difference between scores between different age groups or profession. Conclusions: Lack of adequate knowledge exists in patients who are followed in CTVS OPD when assessed about the basic nature of their disease and drug use. It has been shown that group B had more score which may be due to more education they may have received owing to non-attainment of target INR. This study acts as a baseline and thus advocates the need of proper patient education for patients taking warfarin which may improve the treatment outcome.